(NbOLX[OJ ATLAS kAZAHSTANAs - (NsTRIKALOW(B, (Ni(B. (N`(B.s ((NmOSKWA (B:s (NfEORIQs (NdIZAJN(B. (NiNFORMACIQ(B. (NkARTOGRAFIQ(B,s, 2011)
(NsPRAWO^NO(B-(NKARTOGR(B. (NIZDANIE O PRIRODE(B, (NISTORII(B, (NKULXTURE(B, (NRAZWITII HOZ(B-(NWA(B, (NSOCIAL(B. (NSFERY kAZAHSTANA S DREWNEJ[IH WREMEN(B.s
(NsTRUKTURA IZD(B. : (NwWEDENIE(B; (NkAZAHSTAN SEGODNQ(B; (NpRIRODA(B; (NiSTORIQ(B; (N|TNOGRAFIQ(B; (NsPISOK KART(B; (NuKAZATELX GEOGR(B. (NNAZWANIJ(B.s
(Nw ATLASE NUMERACIQ STRANIC (B- (NNA LEWOJ STORONE RAZWOROTA(B, (NWWERHU(B.s
(NsPISOK KART(B: (NS(B. 874-875 ((NOK(B. 450 (NNAZW(B.)s
Keywords: (NnAUKI O zEMLE (B((NGEODEZI^ESKIE(B, (NGEOFIZI^ESKIE(B, (NGEOLOGI^ESKIE I GEOGRAFI^ESKIE NAUKI(B)s; (NgEODEZI^ESKIE NAUKIs; (NkARTOGRAFIQs -- (NaTLASYs; (NkAZAHSTANs -- (NaTLASs